Co‐designed management scenarios shape the responses of seasonally dry forests to changing climate and fire regimes. Issue 7 (6th May 2020) - Maxwell, Charles J.; Serra‐Diaz, Josep M.; Scheller, Robert M.; Thompson, Jonathan R.
Abstract: Climate change is altering disturbance regimes and recovery rates of forests globally. The future of these forests will depend on how climate change interacts with management activities. Forest managers are in critical need of strategies to manage the effects of climate change. We co‐designed forest management scenarios with forest managers and stakeholders in the Klamath ecoregion of Oregon and California, a seasonally dry forest in the Western US subject to fire disturbances. The resultant scenarios span a broad range of forest and fire management strategies. Using a mechanistic forest landscape model, we simulated the scenarios as they interacted with forest growth, succession, wildfire disturbances and climate change. We analysed the simulations to (a) understand how scenarios affected the fire regime and (b) estimate how each scenario altered potential forest composition. Within the simulation timeframe (85 years), the scenarios had a large influence on fire regimes, with fire rotation periods ranging from 60 years in a minimal management scenario to 180 years with an industrial forestry style management scenario. Regardless of management strategy, mega‐fires (>100, 000 ha) are expected to increase in frequency, driven by stronger climate forcing and extreme fire weather. High elevation conifers declined across all climate and management scenarios, reflecting an imbalance between forest types, climate and disturbance. At lower elevations (<1, 800 m), most scenarios maintained forest cover levels; however, the minimal intervention scenario triggered 5 × 10 5  ha of mixed conifer loss by the end of the century in favour of shrublands, whereas the maximal intervention scenario added an equivalent amount of mixed conifer. Policy implications . Forest management scenarios that expand beyond current policies—including privatization and aggressive climate adaptation—can strongly influence forest trajectories despite a climate‐enhanced fire regime. Forest management can alter forest trajectories by increasing the pace and scale of actions taken, such as fuel reduction treatments, or by limiting other actions, such as fire suppression. Abstract : Forest management scenarios that expand beyond current policies—including privatization and aggressive climate adaptation—can strongly influence forest trajectories despite a climate‐enhanced fire regime. Forest management can alter forest trajectories by increasing the pace and scale of actions taken, such as fuel reduction treatments, or by limiting other actions, such as fire suppression.